2017
DOI: 10.1038/nrg.2017.15
|View full text |Cite
|
Sign up to set email alerts
|

Scaling by shrinking: empowering single-cell 'omics' with microfluidic devices

Abstract: Recent advances in cellular profiling have demonstrated substantial heterogeneity in the behaviour of cells once deemed ‘identical’, challenging fundamental notions of cell ‘type’ and ‘state’. Not surprisingly, these findings have elicited substantial interest in deeply characterizing the diversity, interrelationships and plasticity among cellular phenotypes. To explore these questions, experimental platforms are needed that can extensively and controllably profile many individual cells. Here, microfluidic str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
245
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 293 publications
(246 citation statements)
references
References 155 publications
(259 reference statements)
1
245
0
Order By: Relevance
“…In addition, neutrophil studies using genomics and proteomic approaches are limited by laborious isolation processes and the need for milliliter volumes of blood (≈4–8 mL) to purify sufficient protein and nuclei acid content. While these processes have been successfully miniaturized using microfluidics technologies for sample preparation and high‐throughput “‐omics” analyses, they are still labor intensive and require technical expertise, and thus do not translate easily for bedside testing.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, neutrophil studies using genomics and proteomic approaches are limited by laborious isolation processes and the need for milliliter volumes of blood (≈4–8 mL) to purify sufficient protein and nuclei acid content. While these processes have been successfully miniaturized using microfluidics technologies for sample preparation and high‐throughput “‐omics” analyses, they are still labor intensive and require technical expertise, and thus do not translate easily for bedside testing.…”
Section: Introductionmentioning
confidence: 99%
“…Experimental omics approaches 39,40 to separately process multiple single cells are increasingly important. Four types of approaches are available for partitioning the molecular contents of one cell from another: 1) dilution and separately processing; 2) statistical dilution, tagging and pooling, 41 2) droplet, 42,43 3) micro/nanowell, 21,44 4) microfluidic trapping.…”
Section: Discussionmentioning
confidence: 99%
“…Single‐cell preparations for MS have also provided interesting results, although these techniques can be technically more challenging than, for instance, single‐cell RNA sequencing (Peterson et al, ). Recent advances in single‐cell separation techniques and molecular barcoding (Prakadan, Shalek, & Weitz, ) have unraveled complex interactions and heterogeneous responses among cell types upon stimulation (Satija & Shalek, ; Shalek et al, ; Tirosh et al, ). A detailed description of these novel techniques is outside the scope of the current review, but can be found elsewhere (Svensson, Vento‐Tormo, & Teichmann, ).…”
Section: Tissue Classification and Collectionmentioning
confidence: 99%